2022
DOI: 10.3390/coatings13010059
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Graphene-Based Metamaterials for Terahertz Wave Absorption

Abstract: Graphene-based metamaterials have been widely applied in optoelectronic devices, optical modulators, and chemical sensors due to the outstanding tunability and optical response in the terahertz (THz) region. Here, tunable THz metamaterial absorbers based on patterned graphene are designed, fabricated, and modulated. The proposed metamaterial absorbers are constructed by the top layer of patterned graphene arrays and the aluminum (Al) film separated by polyimide (PI). The different THz absorption spectra can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The most frequently studied photocatalysts for water splitting are graphene-based structures [15,[21][22][23] and polymeric graphite-like carbon nitride g-C 3 N 4 [18,19,24]. Unlike photocatalysts based on transition metal sulfides, g-C 3 N 4 is an environmentally friendly material.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently studied photocatalysts for water splitting are graphene-based structures [15,[21][22][23] and polymeric graphite-like carbon nitride g-C 3 N 4 [18,19,24]. Unlike photocatalysts based on transition metal sulfides, g-C 3 N 4 is an environmentally friendly material.…”
Section: Introductionmentioning
confidence: 99%
“…Some metamaterials regulate terahertz devices by changing the Fermi level, such as two-dimensional materials like graphene and Dirac semi-metals, by applying an external bias voltage and chemical doping, respectively [19][20][21][22]. However, some metamaterials' internal structures change through light, heat, and electricity to achieve changes in material properties, thus realizing the regulation of terahertz devices [23,24]. VO 2 is such a material; its internal structure can be changed by external temperature changes, and it shows different properties (an insulating state and a metallic state) at low and high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Extraordinary research works have been proposed by different researchers to create a low profile with tunable absorbers based on graphene material. Zhou et al [10] suggested a dual-band metasurface absorber using a simple circle-shaped graphene material used as a radiating conductive patch with an overall unit cell size in two dimensions and obtained a maximum absorption percentage of 98.2%. By employing graphene's tunability capability, Li [11], presented broadband and narrow-band absorptivity levels inside the same structure.…”
Section: Introductionmentioning
confidence: 99%